Two forms of replication initiator protein: Positive and negative controls - Wu, Jiazhen (The National Academy of Sciences of the USA, 1997)
The pir gene of plasmid R6K encodes the protein, π, a replication and transcription factor. Two translational options for the pir gene give rise to two forms of π protein: a 35.0-kDa form (π(35.0)) and a shortened 30.5-kDa form (π(30.5)). Although both proteins bind to a series of 22-bp direct repeats essential for plasmid R6K replication, only π(35.0) can bind to a site in the (A⋅T)-rich segment of its γ ori and activate the γ ori in vivo and in vitro. However, unlike π(35.0), π(30.5)can inhibit in vivo and in vitro replication (activated by π(35.0)). We propose that the two forms of π might have distinct functions in replication. We show that although both forms of π produce dimers, the nature of these dimers is not identical. The N-terminal 37 amino acid residues appear to control the formation of the more stable π(35.0) dimers, whereas another, apparently weaker interface holds together dimers of π(30.5). We speculate that the leucine zipper-like motif, absent in π(30.5), controls very specific functions of π protein.